Integrated weed management in Okra - Sainudheen K (Department of Agronomy, College of Horticulture, 2000)
Field experiments were conducted during summer and kharif seasons of 1998 and 1999 at College of Horticulture, Kerala Agricultural University, Thrissur, with the objective of developing an integrated method for management of weeds, especially perennial weeds like Cynodon dactylon (L.) and Cyperus rotundus L. in okra. Broadspectrum herbicide glyphosate, solarization, smother croppmg with cowpea and monthly digging were compared with unweeded control in the summer season, for their effect on weeds. In the subsequent okra crop, during kharif season, different pre-emergence herbicides and farmer's practice of hand weeding were compared with black polyethylene mulching and unweeded control. The experiment was carried out in a split-plot design with three replications, taking summer season treatments as main plots and weed control methods in okra, as sub plots. Cynodon dactylon and Cyperus rotundus were the predominant perennial weeds in the field. Cyperus iria, Digitaria ciliaris, Dactyloctenium aegyptium, Eleusine indica and Ludwigia parviflora were the major annual weeds. In summer season.,) treatments solarization and glyphosate l.2 kg ha-1 were very effective in reducing the weed problems. They also resulted in reduction in the underground vegetative propagules of perennial weeds. Solarization resulted in increasing the soil temperature by 8.5 and 6. 7°C at 5 and 1 0 cm depths respectively, during April. In the subsequent okra crop, black polyethylene mulching gave complete prevention of any weed problems. Among the other combinations, glyphosate 1.2 kg ha" (twice at 45 days interval) during summer season followed by metolachlor l.0 kg ha-1 + HW at 45 DAS in okra crop (in 1998) as well as solarization followed by pendimethalin l.0 kg ha-1 + HW at 45 DAS (in 1999).